An electron microscopic study of spermatogenesis in the drone of scaptotrigona postica (hymenoptera, apidae) - Da cruzlandim, C. [UNESP]; Beig, D. [UNESP] (Taylor & Francis, 1980)
Gonocyst growth in the drone of S. postica is characterized by a series of 5 synchronous mitoses in which cytokinesis is incomplete, and the original cells remain interconnected until spermatozoa formation.During meiosis the division of spermatocytes I was terminated with an anomalous metaphase plate formation at the end of prophase (I). A concentric endoplasmic reticulum encircled the metaphase chromosomes; though microtubuleswere present, spindles were not formed. This abortive division also affected the particular behavior of the centrioles. Although the centrioles proliferated during prophase I, they did not give rise to a spindle, but became associated with the formation of centriolar blebs at cell surface, and seemed eventually to be eliminated.In S. postica, the chromosome number is maintained due to the abortiveness of the first meiotic division; therefore, chromosome distribution is normal during the subsequent division. The second meiotic division resulted in the formation of two spermatids, one of which has a greatly reduced amount of cytoplasm. Nevertheless, bothspermatids formed what look like normal sperm cells. Thus, the Scaptotrigona drone produces 2 rather than 4 sperm cells from each spermatocyte. © 1980 Taylor & Francis Group, LLC.
Keywords: Drone stingless bee; Haploid spermatogenesis; Meliponinae; Ultrastructure